2019
DOI: 10.3389/fimmu.2019.02740
|View full text |Cite
|
Sign up to set email alerts
|

ERα Signaling Increased IL-17A Production in Th17 Cells by Upregulating IL-23R Expression, Mitochondrial Respiration, and Proliferation

Abstract: Women have increased prevalence of Th17-mediated autoimmune diseases, including lupus and multiple sclerosis, and severe asthma. While estradiol and progesterone increased IL-17A production in Th17 cells by inhibiting Let7f miRNA expression and increasing IL-23 receptor (IL-23R) expression, it remained unclear how estrogen signaling through the canonical nuclear receptors, estrogen receptor α (ERα) and/or ERβ, regulated this pathway. We hypothesized that estrogen signaling through ERα increased IL-23R expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 58 publications
1
35
1
Order By: Relevance
“…have shown that neutrophils dimorphism may be modulated by adrenergic stimulation, and that isoprenaline, an adrenergic receptor agonist, binds more efficiently to female neutrophils 34 . In contrast, it is also known that autoimmunity is more prevalent in women, with a possible correlation with the generation of pathogenic Th17 CD4 lymphocytes capable of secreting GM‐CSF 35,36 . It is noteworthy that this has already been addressed in the collagen‐induced arthritis model in which female mice had more severe disease associated with higher frequencies of GM‐CSF‐secreting Th17 cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…have shown that neutrophils dimorphism may be modulated by adrenergic stimulation, and that isoprenaline, an adrenergic receptor agonist, binds more efficiently to female neutrophils 34 . In contrast, it is also known that autoimmunity is more prevalent in women, with a possible correlation with the generation of pathogenic Th17 CD4 lymphocytes capable of secreting GM‐CSF 35,36 . It is noteworthy that this has already been addressed in the collagen‐induced arthritis model in which female mice had more severe disease associated with higher frequencies of GM‐CSF‐secreting Th17 cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptors α and β are expressed in CD4+ T lymphocytes, and their signaling enhances Th1 production of IFN-γ while show variable effects on Th2 production of IL-4 and Th17 production of IL-17A. Estrogen and progesterone increase Th17 cells expression of IL-23R and IL-17A production, as well as increase airway inflammation mediated by IL-17A [12]. [11].…”
Section: Hormones Chromosomes Immunity and Allergymentioning
confidence: 99%
“…while show variable effects on Th2 production of IL-4 and Th17 production of IL-17A. Estrogen and progesterone increase Th17 cells expression of IL-23R and IL-17A production, as well as increase airway inflammation mediated by IL-17A[12].…”
mentioning
confidence: 99%
“…Immune cells furthermore have a critical role beyond host defense in regulating tissue regeneration ( Karin and Clevers, 2016 ; Vivier et al., 2018 ), ranging from ILCs, Th17 cells, and Th22 cells maintaining mucosal integrity ( Chung et al., 2012 ) to natural killer (NK) cells and macrophages shaping the architecture of the placenta ( Vento-Tormo et al., 2018 ). Frequencies of IL-22- and IL-17-producing RORɣt + CD4 + T cells are enhanced in women compared to men and have been shown to be regulated by sex hormones ( Fuseini et al., 2018 , 2019 ; Newcomb et al., 2015 ; Sankaran-Walters et al., 2013 ). IL-22 promotes epithelial stem cell proliferation via STAT3 signaling ( Lindemans et al., 2015 ), contributing to tissue resilience upon damage.…”
Section: Introductionmentioning
confidence: 99%